Distribution, Sources, and Health Risk of Short-, Medium- and Long-Chain Chlorinated Paraffins in School-Area Ambient PM1: A Study from the Pearl River Delta, China - Mo Yang; Xin-Feng Wang; Jing-Wen Huang; Nan-Xiang Jin; Chu Chu; Guo-Feng Huang; Duo-Hong Chen; Min Xie; Yu-Hong Zhai; Yu-Jun Lin; Jun Liu; Li-Zi Lin; et al. (Toxics)
Background: Only a few studies have reported on chlorinated paraffin (CP) levels, especially long-chain chlorinated paraffins (LCCPs), in submicron particulate matter (PM1) in the outdoor air around primary and secondary schools. Methods: This study examined concentrations of short-chain CPs (SCCPs), medium-chain CPs (MCCPs), and LCCPs in PM1 samples from 96 schools across six cities in China’s Pearl River Delta region during the winter (October to December 2018). Results: The median total CP concentration was 34 ng/m3, with median values for SCCP, MCCP, and LCCP of 17.3, 15, and 0.7 ng/m3, respectively. The primary congeners were C13Cl6–8 for SCCPs, C14Cl6–9 for MCCPs, and C18Cl7–10 for LCCPs. The SCCPs and MCCPs largely originated from fugitive dust, whereas the LCCPs were mainly sourced from organic chemical industries. Air masses from the South China Sea contributed most to SCCP and MCCP levels, while those from the east coast accounted for the highest LCCP levels. The concentrations of CP in PM1 were significantly positively correlated with PM1 levels. Conclusions: The exposure risk assessments by age indicated a very low current health risk from PM1-related CP inhalation, although prolonged pollution could raise these risks as CP concentrations in ambient PM may continue to increase.